2008
DOI: 10.1007/s11126-008-9083-1
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use by Patients with Psychiatric Disorders in Search for General and Medical Informations

Abstract: Internet is currently used by patients treated for psychiatric disorders, especially for medical seeking information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 14 publications
3
68
1
3
Order By: Relevance
“…8,20,26,28,34,36 However, social media are reported to have broken down some of these socioeconomic disparities, as their use is not restricted by race, ethnicity, income, education level, or geographic location. 5,28,30 The current study also found no correlation between social media use and race, income, or geographic location.…”
Section: Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…8,20,26,28,34,36 However, social media are reported to have broken down some of these socioeconomic disparities, as their use is not restricted by race, ethnicity, income, education level, or geographic location. 5,28,30 The current study also found no correlation between social media use and race, income, or geographic location.…”
Section: Social Mediamentioning
confidence: 99%
“…2,38 While physicians are the preferred source of information, 9,13,22,35,40 in reality, caregivers turn to the Internet for answers first, especially for rare and chronic conditions. 9,13 While Internet use is becoming nearly universal, the Pew Internet and American Life Project, 8,11,18,36 Health Information National Trends Survey (HINTS), 22,26,28 and disease-specific studies 2,6,20,34,37,39 have found that socioeconomic disparities create a digital divide between patient populations. Interestingly, use of social media is reported to permeate all race, economic, and educational strata.…”
mentioning
confidence: 99%
“…[1,2] For example, a survey of the British population revealed that 18% of all Internet users had sought online information related to mental health, with a higher prevalence among those with a past history of mental health problems. [3] In the same vein, Khazaal et al [4] revealed that 68.5% of patients followed in an outpatient psychiatric unit used the Internet to find health-related information.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that young men feel more comfortable contacting a call centre instead of directly facing a healthcare professional. This is in line with mental health patients' preference for anonymous sources for health and medicines information [33][34][35].…”
Section: Characteristics Of (Antipsychotic) Medication Information Sementioning
confidence: 55%